2000
DOI: 10.1016/s0735-1097(00)00616-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of endothelial function and insulin sensitivity with vitamin C in patients with coronary spastic angina

Abstract: Vitamin C improves both endothelial function and insulin sensitivity in patients with CSA. Thus, reactive oxygen species and/or decreased nitric oxide bioactivity may play an important role in the genesis of both endothelial dysfunction and insulin resistance in patients with CSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 37 publications
6
65
0
Order By: Relevance
“…Consistent with this hypothesis, intravenous infusion of ascorbic acid to glucose intolerant subjects and smokers improved FMD and insulin sensitivity while reducing plasma thiobarbituric acid-reactive substances, an index of lipid peroxidation. 42 Similarly, Hirashima et al 43 reported that in patients with vasospastic angina, a condition associated with reductions in insulin sensitivity 44 and NO status, 45 ascorbic acid infusion normalized FMD and reduced insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with this hypothesis, intravenous infusion of ascorbic acid to glucose intolerant subjects and smokers improved FMD and insulin sensitivity while reducing plasma thiobarbituric acid-reactive substances, an index of lipid peroxidation. 42 Similarly, Hirashima et al 43 reported that in patients with vasospastic angina, a condition associated with reductions in insulin sensitivity 44 and NO status, 45 ascorbic acid infusion normalized FMD and reduced insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Enhanced insulin sensitivity has been demonstrated by treatment with LA [84], vitamin E [87], and vitamin C [88] in small-sized, short-term trials. However, these results have not been confirmed in other studies.…”
Section: Therapeutic Approaches To Reduce Oxidative Stressmentioning
confidence: 99%
“…Insulin sensitivity, assessed by steady state plasma glucose method, was impaired in patients with coronary spastic angina as compared with control subjects. Antioxidants, such as vitamin C, can improve the insulin sensitivity and endothelial function in patients with coronary spastic angina (69). Thus, reactive oxygen species and/or decreased nitric oxide bioactivity may play a significant role in the genesis of both endothelial dysfunction and insulin resistance in patients with coronary spasm.…”
Section: Coronary Spasm and Insulin Sensitivitymentioning
confidence: 99%